Socialist urbanisation and social segregation - Čaldarović, Ognjen (Array, 1992)
In the chapter major aspects of post-second war developments concerning urbanization and residential segregation are presented. Major results from different urban sociology researches are also presented, with an emphasis on housing conditions, especially in mass housing units in new towns and new settlements.